Transcriptional and electrical identity in endothelial cells is orchestrated by intercellular coupling - Burboa, Pía C.; Kuzdowicz, Veronica; Ordenes, Stefany; Sánchez, Helmuth A.; Lillo, Mauricio A. (Frontiers in Physiology, 2025)
The membrane potential (Vm) of vascular cells is a fundamental determinant of vasomotor tone, particularly in resistance arteries and arterioles where precise electrical signaling ensures tissue perfusion and blood pressure regulation. While the electrophysiological role of vascular smooth muscle cells is well characterized, the bioelectrical contribution of endothelial cells (ECs)—especially their Vm dynamics, calcium responsiveness, and transcriptional plasticity—remains incompletely understood. Here, we combined intracellular microelectrode recordings, calcium imaging, RNAscope, and immunofluorescence to dissect the transcriptional and electrical landscape of ECs in murine mesenteric arterioles and primary cultures. ECs cultured in isolation exhibited a depolarized Vm (∼–25 mV), disrupted ion channel organization, and reduced expression of key regulators, including FOXO3, MEF2C, KCa2.3, KCa3.1, and Kir2.1. Functionally, these cells failed to hyperpolarize or elevate intracellular calcium in response to acetylcholine (ACh) or the KCa channel activator SKA-31. In contrast, electrically coupled ECs displayed a more negative and heterogeneous Vm (−65 mV to −40 mV), robust hyperpolarization, and markedly enhanced calcium responses. This phenotype correlated with spatially coordinated upregulation of ion channels and transcription factors, as shown by RNAscope and immunofluorescence, supporting the existence of a coupling-dependent transcriptional program that sustains endothelial bioelectrical competence. Strikingly, time-resolved heatmaps and 3D activity maps revealed that coupled EC generate synchronized calcium waves upon ACh stimulation, with greater ΔF/F0 amplitudes and spatiotemporal coordination compared to non-coupled counterparts. These organized calcium dynamics mirrored peripheral ion channel clustering and supported a hyperpolarization-competent phenotype. Consistently, a subpopulation (∼30%) of ECs in coupled conditions exhibited Vm values below −55 mV. Supporting our findings, endothelium removal in intact arterioles abolished the hyperpolarized Vm component and depolarized the vessel wall toward −30 mV, indicating that the endothelium plays a dominant role in setting arteriolar membrane potential. Altogether, our data uncover a transcriptionally regulated, calcium-sensitive, and electrically competent endothelial phenotype that critically depends on cell–cell coupling. We propose that connexin-mediated communication not only enables ionic and metabolic exchange but also synchronizes transcriptional programs that define endothelial identity and ensure vascular integration. Disruption of this electro-transcriptional coupling may represent an early hallmark of endothelial dysfunction and impaired vasodilatory conduction. These findings offer a mechanistic framework for identifying early-stage biomarkers and therapeutic targets aimed at preserving endothelial integrity in cardiovascular disease.